Non-isolated high step-up DC/DC converters - An overview - Koc, Yavuz; Birbir, Yasar; Bodur, Haci (ELSEVIER, 2022)
High step-up, high efficiency, low cost DC/DC converters have operated as an interface to make use of the renewable energy system generated power. In order to obtain desired output voltage, the DC/AC voltage conversion to AC mains voltage is an important consideration mainly achieved through inverters. Taking into acoount the performance of the non-isolated high step-up DC/DC converters for the renewable energy systems, the substantial amount of topologies studied in past years are the non-isolated high step-up DC/DC converters. Based on proposed and generalized configurations, the non-isolated high step-up DC/DC converters are classified into several categories and reviewed in this paper. So, to clarify the distinguishing solutions, the key features; topological variations, merits and demerits of these converters are discussed and compared. This review work aims to give a well-informed and a well-detailed general framework about these converters and facilitates to derive the new well topologies in the future. (C) 2021 THE AUTHORS. Published by Elsevier BV on behalf of Faculty of Engineering, Alexandria University.
Keywords: DC/DC converter; High step-up; Coupled inductor; Renewable energy; Soft switching; Gain cell; DC-DC CONVERTER; HIGH-VOLTAGE-GAIN; INTERLEAVED BOOST CONVERTER; 3-WINDING COUPLED-INDUCTOR; SLIDING-MODE CONTROL; HIGH-EFFICIENCY; SINGLE-SWITCH; PWM CONVERTERS; STEADY-STATE; CELL; Engineering